บทบาทหน้าที่การกำกับและส่งเสริมกิจการสถานศึกษา ของคณะกรรมการสถานศึกษาขั้นพื้นฐาน อำเภอผาขาว สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 2 - คำทอง บุญมี; ศรจันทร์ ชิษณพงศ์; พจนธารี อิสรียา (Ratchaphruek Journal, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการมีส่วนร่วมในการปฏิบัติตามบทบาทหน้าที่การกำกับและส่งเสริมกิจการสถานศึกษา และเปรียบเทียบการมีส่วนร่วมในการปฏิบัติตามบทบาทหน้าที่การกำกับและส่งเสริมกิจการสถานศึกษาของคณะกรรมการสถานศึกษาขั้นพื้นฐาน อำเภอผาขาว สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 2 กลุ่มตัวอย่างที่ใช้ในการวิจัย ได้แก่ คณะกรรมการสถานศึกษาขั้นพื้นฐาน จำนวน 162 คน ซึ่งกำหนดขนาดกลุ่มตัวอย่างโดยใช้ตารางเครจซี่และมอร์แกน (Krejcie and Morgan) โดยวิธีการสุ่มแบบอย่างง่าย เครื่องมือที่ใช้ในการวิจัยคือแบบสอบถาม เป็นมาตราส่วนประมาณค่า 5 ระดับ จำนวน 40 ข้อ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน t-test และF-test ผลการวิจัย พบว่า 1. การมีส่วนร่วมในการปฏิบัติตามบทบาทหน้าที่ในการกำกับและส่งเสริมกิจการสถาน ศึกษาของคณะกรรมการสถานศึกษาขั้นพื้นฐาน อำเภอผาขาว สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 2 โดยภาพรวมและรายด้านทุกด้านอยู่ในระดับมาก ด้านที่มีค่าเฉลี่ยมากที่สุดคือ ด้านวิชาการ รองลงมาคือ ด้านงบประมาณ ด้านการบริหารงานบุคคล และด้านการบริหารทั่วไป ตามลำดับ 2. ผลการเปรียบเทียบการมีส่วนร่วมในการปฏิบัติตามบทบาทหน้าที่การกำกับและส่งเสริมกิจการสถานศึกษาของคณะกรรมการสถานศึกษาขั้นพื้นฐาน อำเภอผาขาว สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 2 จำแนกตามสถานภาพของคณะกรรมการสถานศึกษาขั้นพื้นฐาน พบว่า ไม่แตกต่างกัน จำแนกตามขนาดสถานศึกษาที่ปฏิบัติงานพบว่าทั้ง 3 ด้านไม่แตกต่างกัน ส่วนด้านการบริหารงานบุคคล แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 จึงทำการวิเคราะห์ความแตกต่างของค่าเฉลี่ยเป็นรายคู่ด้วยวิธีการของเชฟเฟ่ (Scheffé) พบว่าขนาดของสถานศึกษาขนาดเล็กแตกต่างกันกับขนาดใหญ่ ส่วนนอกนั้นไม่พบความแตกต่างเป็นรายคู่ The Roles of the School Board in Supervision and Promotion of Schools in Pha Khao District under the Office of Loei Primary Education Service Area 2 The objectives of this research were to study the participation of the basic education school board, and to compare the participation of the basic education school board, Pha Khao District, under Loei Primary Education Service Area Office 2 in performing roles and duties of school activity supervision and promotion. The research subjects consisted of 162 members of the basic education school board. Krajcie and Morgan’s tubular technique and the simple random sampling tool employed the sample size. The research tool used to collect data was the five rating scale questionnaires, contained 40 items. The alpha coefficient of reliability and the content validity (IOC) of the questionnaire were divided into two types of analyzing statistics: the descriptive one, which was frequency, percentage, mean and standard deviation, and the inferential one, which was the paired t-test and one-way analysis of variance (ANOVA) by F-test. The research findings were as follows: 1. The participation of the basic education school board was found overall and in each aspect at a high level. The academic aspect had the highest average score, followed by the budget, the personnel administration and the general administration, respectively. 2. The comparison result of the participation was found to be indifferent, when it was classified by the status of the basic education school board. When it was classified by the school sizes, academic aspects, the budget and the general management, they were found to be different, while the personnel administration revealed the difference at a statistically significant level of 0.05. Then, Scheffé’s method of paired comparison was utilized and it was found that a small sized school was different from the size of a big sized one while others were different in paired comparison.